Analiza poselitve glede na geomorfološke značilnosti z metodo Monte Carlo - Podobnikar, Tomaž (Geografski vestnik, 2000)
New approaches include more and more non-spatial statistical techniques adapted for solving the spatial analyses tasks in geographic information systems. An example of such techniques is the Monte Carlo method. In the article it is represented with the case of testing statistical significance of the spatial point patterns regarding to geomorphological characteristic in the case study area of Polhograjsko hribovje (Polhov Gradec hills) spatial distributin of houses and population with regard to the distance from water springs and streams, height above sea level, relief slope, relief incline, relief aspect, relief insolation and karst is tested. Results of the empirical Monte Carlo tests are compared with traditional statistical tests.
Keywords: informacijski sistemi; geografski informacijski sistemi; prostorski informacijski sistemi; metoda Monte Carlo; Monte Carlo method; geomorfologija; geomorphology; poselitev; naselja; Slovenia; Slovenija; Polhograjsko hribovje; Polhov Gradec Hills